Zhodnocení a návrhy na zlepšení poskytování hypotéčních úvěrů v Raiffeisenbank, a.s. - Kaštyl, Petr (Vysoké učení technické v Brně. Fakulta podnikatelská, 2007)
Předmětem diplomové práce je zanalyzování stávajícího stavu, nalezení případných nedostatků a navrhnutí konkrétních kroků ke zlepšení v poskytování hypotečních úvěrů v Raiffeisenbank, a.s. s cílem zvýšení konkurenceschopnosti společnosti v oblasti hypotečního bankovnictví. Hodnocení a návrhy na zlepšení jsou prováděny v několika dílčích celcích, a to v oblasti technických parametrů, úvěrového procesu a podpory prodeje. Dílčím cílem je navrhnutí nového produktu k rozšíření současné nabídky.

The master’s thesis deals with the analysis of the present state, the finding of the contingent deficiencies and the presentation of the improvement suggestions including the concrete measures in granting mortgage credits by Raiffeisenbank, Inc. with a view to advance the competitive strength of the company in the field of mortgage banking. The evaluation and the improvement suggestions are conducted in several component units: in the fields of technical parameters, credit procedure and sales promotions. A partial aim of the thesis concerns the introduction of a new product for the extension of the current supply.
The Evaluation and Proposals for the Improvement of Extending Motrage Credits in Raiffeisenbank, a.s
Keywords: hypoteční úvěr; technické parametry hypotečních úvěrů; úvěrový proces; variabilní hypotéka; hypotéka pro mladé; mortgage credit; technical parameters of mortgage credits; credit procedure; variable mortgage; mortgage destined for young people